Stratigraphic Architecture and Computer Modelling of Carbonate Platform Margin, Late Ordovician Lianglitage Formation, Central Tarim Basin - 李浩 林畅松 张燕梅 张荣茜 芮志峰 黄理力 (Journal of earth science (Wuhan, China), 2012)
According to the different geometries and reflected characteristics in the seismic sections, the carbonate platform margin of the northern slope can be summarized as three basic depositional architectures in the Late Ordovician Lianglitage （良里塔格） Formation of the Tazhong （塔中） uplift. The type one mainly located in the west of the carbonate platform margin, and it showed obvious imbricate progradation from the interior to the margin of the platform. The type two was in the middle of the carbonate platform margin, which showed retrogradational stacking pattern in the same transgres- sive systems tract period, and the slope strata of the platform margin showed progradational sequence in the highstand systems tract period. The type three located in the east of the carbonate platform margin, and it showed the parallel aggradational architecture. The crossing well section along the northern slope of the Tazhong carbonate platform showed that the depositional thickness became thinner from the east to the west. The thickest belt located in the east of the platform margin, and became thinner rapidly towards the basin and the platform interior. These indicated that the paleogeomorphology ofthe Tazhong uplift was probably high in the west and low in the east during the period of the Late Ordovician Lianglitage Formation. According to the interpretation of seismic profiles and the computer modelling result, the depositional architectures of sequence O31-2 showed aggradation, retrogradation and progradation from the east to the west of the carbonate platform margin during the transgression period. This meant that the accommodation became smaller gradually from the east to the west along the northern carbonate platform margin of the Tazhong uplift.The difference of the accommodation was probably caused by the difference of tectonic subsidence. Also, computer-aided modelling can be used to deeply understand the importance of various control parameters on the carbonate platform depositional architectures and processes.